Legal Consequences for Creditors Caused by Forced Withdrawal of Fiduciary Objects - Ryan Ari Hadinata (NORMA, 2021)
The researcher used the title Legal Consequences for Creditors Caused By Forced Withdrawal Of Fiduciary Objects. The formulation of the problems that arise includes, among others: what the creditor can take legal actions if the debtor does not pay the debt when it is due and what are the legal consequences faced by the creditor for the debtor's legal action related to the forced withdrawal of the object of fiduciary security by the creditor, The form of this research method is normative legal research, so in this study, an approach to legislation along with views and doctrines in legal science is analysed which is then analysed against the application of Law to resolve legal issues in this study. From the result the analysis carried out in this study, the researcher states that: as a result of the creditor executing the object of fiduciary security by force when the debtor defaults, it can be subject to criminal sanctions contained in Articles 335, 365, and 368 of the Criminal Code related to using coercion and physical violence and in Article 3 paragraph 1 of the Regulation of the Minister of Finance of the Republic of Indonesia Number 130/PMK.010/2012 which also imposes sanctions on financial institutions that do not register the object of guarantee at the fiduciary guarantee registration office. As for the things that underlie the parties to take legal action, namely: the creditor wants the debtor's obligations to be carried out correctly to pay off his debt. In contrast, the debtor wants to get protection against the forced withdrawal of the object of the guarantee carried out by the creditor.Keywords: Guarantee, Execution, Fiduciary